The Impact of Using E-Commerce and Accounting Information Systems on Financial Performance in MSMEs - Fitri Indah Sari M; Manda HM; Zainal Abidin; Ikhsan Amar Jusman (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
This study aims to analysed the impact of using e-commerce and accounting information systems on financial performance in MSMEs in Makassar city. The population used in the study were MSMEs in the Tangerang area by taking a sample of 120 MSMEs with a purposive sampling method with the criteria that MSMEs that sell using e-commerce for at least 1 (one) year and use accounting applications for financial recording. The type of data is primary data sourced from the results of the questionnaire. The data analysis methods used in this study are Classical Assumption Test, Multiple Linear Regression Test, t test, and f test. The results of this study indicate that simultaneously e-commerce and accounting information systems affect financial performance in MSMEs in Makassar city. Partially e-commerce has a positive effect on financial performance, besides that the financial information system has a positive effect on financial performance in MSMEs in Makassar city.